Brazilian contributions to the advancement of laparoscopic surgery: an analysis of the evidence - de Lacerda, Dhiego Alves; Lima, Larissa Luana Lopes; Honorato, Pedro Fechine; Vale, Renata Braga; das Neves, Diego Formiga; de Sá Filho, Claudenor Pinho; de Moura, Thiago Quirino; Figueiredo, Vinícius Costa; de Oliveira, Anaylle Vieira Lacerda; Isidório, Ubiraídys de Andrade (Revista Sistemática, 2024)
Laparoscopic surgery has been a revolution in surgical practice worldwide, providing substantial benefits to patients, such as shorter recovery time, less postoperative pain, and reduced hospital stay. In the Brazilian context, marked by the diversity of clinical conditions and resource limitations, the adoption and advancement of laparoscopic surgery have been the target of intensive study and research.